Dual-mode stimuli-responsive polymer, anti-counterfeiting film and preparation method of dual-mode stimuli-responsive polymer

By adopting the preparation method of dual-mode stimulation-responsive polymers in color-changing polymer materials, the problems of material thermal stability and mechanical properties are solved, and the rapid, reversible, dual-mode color and fluorescence response of the material under external stimulation are achieved, which improves the safety and functionality of the anti-counterfeiting material.

CN119591866APending Publication Date: 2025-03-11SOUTHWEAT UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411682035.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing color-changing polymer materials are prone to damage the thermal stability and mechanical properties of the material during the preparation process, and most anti-counterfeiting materials exhibit a single function, resulting in a lower level of safety.

Method used

A dual-mode stimulation responsive polymer is adopted, with a structural formula of which n is 30. The polymer is prepared by a specific synthetic method, including reaction using raw materials such as p-nitrobenzenesulfonyl chloride, aluminum chloride and bromide, and precipitation and purification through sodium polysulfate solution and Na2S·9H2O and other media, and finally, the polymer is prepared by high-temperature reaction under nitrogen conditions.

Benefits of technology

The polymer has excellent thermal stability (T5% = 463°C, Tg = 245°C), exhibits fast, high contrast, dual mode and reversible color and fluorescence response to external stimuli, and can be added to traditional polymer materials as trace additives, improving its anti-counterfeiting ability without affecting mechanical and thermal properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FDA0005148583480000011
    Figure FDA0005148583480000011
  • Figure HDA0005148583500000011
    Figure HDA0005148583500000011
  • Figure HDA0005148583500000012
    Figure HDA0005148583500000012
Patent Text Reader

Abstract

The invention discloses a dual-mode stimuli-responsive polymer, an anti-counterfeiting film and a preparation method of the dual-mode stimuli-responsive polymer, and belongs to the technical field of preparation of anti-counterfeiting films.The preparation method of the polymer comprises the steps that p-nitrobenzenesulfonyl chloride, aluminum chloride and bromobenzene are stirred and mixed to be uniform, the mixture is heated to react, a reaction solution is placed in ice water to separate out precipitates, and drying and purifying are conducted to obtain the dual-mode stimuli-responsive polymer. Preparing an intermediate 1; na2S. 9H2O, powdered sulfur and deionized water are added into a sodium polysulfate solution to be dissolved, and a sulfur-containing solution is prepared; adding the intermediate 1 into a sulfur-containing solution, heating for reaction, collecting precipitate, removing excessive sodium polysulfate, and purifying to obtain an intermediate 2; under the nitrogen condition, uniformly mixing the intermediate 2, NaOt-Bu, Pd2 (dba) 3, BINAP and N, N-dimethylformamide, heating for reaction, putting into ice water to separate out precipitate, and purifying to obtain the PdBu / BINAP composite material. The material can effectively solve the problem that the existing material damages the thermal stability and mechanical properties of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of stimulus-responsive compounds, and in particular relates to a dual-mode stimulus-responsive polymer, an anti-counterfeiting film and a preparation method thereof. Background Art

[0002] With the acceleration of global economic integration, the proliferation of counterfeit and shoddy products and information leakage have become undeniable global problems. This phenomenon not only seriously erodes the value of intellectual property rights, but also poses a serious challenge to the market order and causes inestimable economic losses. In this context, it is urgent to strengthen anti-counterfeiting and encryption technology. With the acceleration of technological progress, counterfeiting methods are evolving into more complex forms. Traditional anti-counterfeiting technologies such as watermarks, lasers, inkjet printing, and fluorescence have begun to expose their limitations - poor adaptability, easy to be imitated, high technical barriers, and high costs. Therefore, there is an urgent need to explore and develop new anti-counterfeiting and encryption technologies that are efficient, anti-copying, and cost-effective. This pursuit is essential to promote strong and sustainable market development while safeguarding consumer rights.

[0003] Among the many anti-counterfeiting materials, stimuli-responsive color-changing polymers stand out for their unique properties such as stimuli responsiveness, structural design flexibility, low specific gravity, excellent chemical stability, easy processing and cost-effectiveness, making them the leader in anti-counterfeiting materials. The focus of research and cutting-edge applications in the field of anti-counterfeiting. These materials respond to specific external stimuli, such as light, temperature changes and pH fluctuations, and exhibit obvious color changes, providing simple and recognizable anti-counterfeiting marks. However, the current strategies for preparing color-changing polymer materials face major challenges. First, the physical doping method mixes small molecule color-changing dyes with polymer matrices, which, although simple to operate, often compromises the thermal stability and mechanical properties of the materials. Second, complex chemical synthesis methods involve covalently bonding color-changing groups to polymers while enhancing stability, but have proven to be costly and require complex synthetic pathways. In addition, most anti-counterfeiting materials based on stimuli-responsive color-changing polymers usually exhibit a single function, resulting in a relatively low level of security and limited applications. Therefore, creating multi-mode stimuli-responsive color-changing polymer materials from the perspective of the intrinsic molecular structure is an effective way to solve this problem. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the present invention provides a dual-mode stimulus-responsive polymer, an anti-counterfeiting film and a preparation method thereof, which can effectively solve the problem of existing materials damaging the thermal stability and mechanical properties of the materials.

[0005] To achieve the above purpose, the technical solution adopted by the present invention to solve the technical problem is:

[0006] A dual-mode stimulus-responsive polymer, the structural formula of the polymer is:

[0007] Among them, n is 30.

[0008] The method for preparing the dual-mode stimulus-responsive polymer comprises the following steps:

[0009] (1) p-nitrobenzenesulfonyl chloride, aluminum chloride and bromobenzene are stirred and mixed, and the mixture is heated to react. After the reaction is completed, the reaction solution is placed in ice water to precipitate, and the precipitate is dried and purified to obtain intermediate 1;

[0010] (2) adding Na2S·9H2O, sulfur powder and deionized water to a sodium polysulfate solution and heating until dissolved to prepare a sulfur-containing solution;

[0011] (3) adding the intermediate of step (1) to the sulfur-containing solution of step (2), heating for reaction, collecting the precipitate after the reaction, removing the excess sodium polysulfate, and purifying to obtain intermediate 2;

[0012] (4) Under nitrogen conditions, the intermediate 2, NaOt-Bu, Pd2(dba)3, BINAP and N,N-dimethylformamide were mixed and heated to react. After the reaction was completed, the mixture was placed in ice water to precipitate, and purified to obtain the product.

[0013] Among them, BINAP is 1.1'-binaphthyl-2.2'-diphenylphosphine.

[0014] Furthermore, in step (1), the heating reaction temperature is 55-65° C., and the reaction time is 5-7 h.

[0015] Furthermore, in step (3), the heating reaction temperature is 90-94° C., and the reaction time is 2-3 h.

[0016] Furthermore, ethanol is used for recrystallization purification in step (1) and step (3).

[0017] Furthermore, in step (4), the heating reaction temperature is 125-135° C., and the reaction time is 11-13 h.

[0018] Furthermore, methanol is used for recrystallization purification in step (4).

[0019] Application of the above-mentioned dual-mode responsive polymer in the preparation of anti-counterfeiting materials.

[0020] A dual-mode responsive anti-counterfeiting film comprises the dual-mode stimulus responsive polymer.

[0021] Furthermore, the method comprises the following steps: adding PIS to a polymer matrix solution, stirring and mixing to obtain a mixture solution, coating the mixture solution on a substrate, and drying to obtain the mixture solution.

[0022] The beneficial effects produced by the present invention are:

[0023] 1. The polymer prepared by the present invention has excellent thermal stability (T5% = 463°C, Tg = 245°C) and exhibits rapid, high-contrast, dual-mode and reversible color and fluorescence responses to external stimuli.

[0024] 2. The polymer can be added as a trace additive to traditional polymer materials to transform traditional polymers into materials with intrinsic anti-counterfeiting capabilities, giving traditional polymer materials dual-mode color / fluorescence transformation; at the same time, the addition of the polymer will not affect the mechanical and thermal properties of traditional polymer materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is the reaction process diagram in Example 1;

[0026] Figure 2 is a characterization diagram of the intermediate 2 obtained in Example 1, wherein a is 1 H NMR diagram, b is 13 C NMR graph, c its FTIR graph;

[0027] Figure 3 is a characterization diagram of the PIS prepared in Example 1, wherein a is 1 H NMR diagram, b is 13 C NMR graph, c its FTIR graph;

[0028] Figure 4 The Gaussian calculation results of the model compounds are shown in Figure a, where Figure b is the calculation result of the nitrogen anion (transition state), and Figure c is the calculation result of the quinone;

[0029] Figure 5 UV-visible spectra of PIS and PIS-NaOt-Bu;

[0030] Figure 6 is the cyclic UV spectrum of PIS;

[0031] Figure 7 The structure and color change diagram of PIS after the introduction of NaOt-Bu and CF3COOH;

[0032] Figure 8 The wavelength variation diagram of the maximum absorption peak in 10 cycles;

[0033] Fig. 9 The fluorescence comparison diagram of PIS and PIS-NaOt-Bu;

[0034] Fig.10 is the cyclic fluorescence spectrum of PIS;

[0035] Fig.11 This is the maximum emission peak wavelength variation diagram within 10 cycles;

[0036] Fig.12 is the fluorescence spectra of PIS at different concentrations;

[0037] Fig.13 is the thermal performance diagram of PIS, where a is the TGA curve of PIS, and b is the thermal performance of PIS and other stimuli-responsive color-changing materials (T 5% ) figure, c is the DSC curve of PIS, d is the glass transition temperature diagram of PIS and other stimuli-responsive color-changing materials;

[0038] Fig.14 A double encryption confidentiality diagram for the color / fluorescence dual-mode stimulus response characteristics; where a is the information status diagram in the encrypted state, b is the information display diagram under ultraviolet light after adding different solutions, b is the information display diagram under visible light after adding alkaline solution, and d is the information display diagram under ultraviolet light after adding alkaline solution;

[0039] Fig.15 Schematic diagram of the preparation of EPD-x% film and its stimulation changes;

[0040] Fig.16 The color change diagram of EPD-x% film under visible light and ultraviolet light after stimulation under alkaline conditions;

[0041] Fig.17 The fluorescence change diagram of EPD-0.3% film under alkali and acid stimulation over time;

[0042] Fig.18 To obtain the authenticity verification diagram of reversibility through painting;

[0043] Fig.19 is the stress-strain curve of EPD-x% film;

[0044] Fig. 20 DSC curve of EPD-x% film;

[0045] Fig.21 This is the TGA curve of the EPD-x% film. DETAILED DESCRIPTION

[0046] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all of the embodiments.

[0047] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present invention.

[0048] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.

[0049] The features and performance of the present invention are further described in detail below in conjunction with the embodiments and drawings.

[0050] Example 1

[0051] A dual-mode stimulus-responsive polymer, the preparation method of which comprises the following steps:

[0052] (1) 3 g (13.5 mmol) of p-nitrobenzenesulfonyl chloride, 1.67 g (12.5 mmol) of aluminum chloride and 8 mL of bromobenzene were added to a 50 mL two-necked flask, stirred at room temperature for 2 h, and then slowly heated to 60° C. for 6 h. After the reaction was completed, the reaction solution was poured into ice water and stirred for 30 minutes. After the precipitated solid (light yellow) no longer increased, it was filtered and vacuum dried (60° C., 10 h) to obtain crude 4-bromo-4'-nitrodiphenyl sulfone (BNDPS), which was purified by recrystallization from ethanol to obtain 4-bromo-4'-nitrodiphenyl sulfone (BNDPS), i.e., intermediate 1;

[0053] (2) 3.23 g (13.45 mmol) of Na2S·9H2O, 0.52 g (16.25 mmol) of sulfur powder and 25 mL of deionized water were added to a 50 mL double-necked flask containing 0.5 mol / L sodium polysulfate (Na2S2) solution, and then heated to 90°C to completely dissolve the sublimated sulfur powder to prepare a sulfur-containing solution;

[0054] 2.24 g of BNDPS was added to a 100 mL double-necked flask, and then the sulfur-containing solution was slowly added and heated to 92 ° C for 2.5 h. After the reaction was completed, the excess Na2S2 was removed by water washing and vacuum drying (60 ° C, 10 hours), and 4-bromo-4'-aminodiphenyl sulfone (BADPS) was obtained by recrystallization and purification with ethanol, i.e., intermediate 2. The characterization results are shown in Figure 2 ;

[0055] in, 1 H NMR (600MHz, DMSO-d6): δ = 7.79 (dd, J = 7.74, 9.00Hz, 4H), δ = 7.57 (d, J = 8.44Hz, 4H), δ = 6.65 (d, J = 8.34Hz, 2H), δ = 6.26 (s, 2H) ppm;

[0056] 13 C NMR (600MHz, DMSO-d6): δ=154.2, 143.0, 132.9, 129.9, 128.9, 126.8, 124.9, 113.4ppm;

[0057] FTIR (KBr particles, cm -1 ): 3478, 3384 (-NH-), 1294, 1149 (sulfacyl), 1589 (benzene ring), 832 (para-substituted benzene ring);

[0058] (3) Under nitrogen conditions, 8 mmol BADPS, 12 mmol NaOt-Bu, 0.04 mmol Pd2(dba)3, 0.12 mmol BINAP and 20 mL N,N-dimethylformamide were added to a 50 mL three-necked flask in sequence, mixed, and then heated to 130°C for continuous reaction for 12 hours. After the reaction, the obtained polymer solution was poured into ice water and stirred to precipitate a brown solid. The filter cake was filtered and washed with water to obtain a filter cake, which was dried in a vacuum drying oven. The dried filter cake was extracted with methanol as an extractant using a Soxhlet extraction apparatus for 12 hours to remove unreacted small molecules and impurities. After vacuum drying, polyiminosulfone (PIS) was obtained;

[0059] The above reaction process can be seen in Figure 1 The results are shown in Figure 3 ;

[0060] in, 1 H NMR (600MHz, DMSO-d6): δ = 9.39 (s, 1H), δ = 7.77 (d, J = 8.40Hz, 4H), δ = 7.26 (d, J = 8.38Hz, 4H) ppm;

[0061] 13 C NMR (600MHz, DMSO-d6): δ=146.3, 133.2, 129.2, 117.4ppm;

[0062] FT-IR (KBr particles, cm -1 ): 3418 (-NH-), 1294, 1146 (sulfacyl), 1582 (benzene ring), 822 (para-substituted benzene ring).

[0063] Gel permeation chromatography (GPC) analysis showed that the number average molecular weight (Mn) of PIS was 3500 g / mol.

[0064] The weight average molecular weight (Mw) was 7233 g / mol and the polydispersity index (PDI) was 2.07.

[0065] Example 2

[0066] A dual-mode stimulus-responsive polymer, the preparation method of which comprises the following steps:

[0067] (1) 3 g (13.5 mmol) of p-nitrobenzenesulfonyl chloride, 1.67 g (12.5 mmol) of aluminum chloride and 8 mL of bromobenzene were added to a 50 mL two-necked flask, stirred at room temperature for 2 h, and then slowly heated to 55° C. for 7 h. After the reaction was completed, the reaction solution was poured into ice water and stirred for 30 minutes. After the precipitated solid (light yellow) no longer increased, it was filtered and vacuum dried (60° C., 10 h) to obtain a crude product of 4-bromo-4'-nitrodiphenyl sulfone (BNDPS), which was purified by recrystallization from ethanol to obtain 4-bromo-4'-nitrodiphenyl sulfone (BNDPS), i.e., intermediate 1;

[0068] (2) 3.23 g (13.45 mmol) of Na2S·9H2O, 0.52 g (16.25 mmol) of sulfur powder and 25 mL of deionized water were added to a 50 mL double-necked flask containing 0.5 mol / L sodium polysulfate (Na2S2) solution, and then heated to 90°C to completely dissolve the sublimated sulfur powder to prepare a sulfur-containing solution;

[0069] 2.24 g of BNDPS was added to a 100 mL double-necked flask, and then the sulfur-containing solution was slowly added and heated to 90 ° C for 3 h. After the reaction was completed, the excess Na2S2 was removed by water washing and vacuum drying (60 ° C, 10 hours), and 4-bromo-4'-aminodiphenyl sulfone (BADPS) was obtained by recrystallization and purification with ethanol, i.e., intermediate 2. The characterization results are shown in Figure 2 ;

[0070] (3) Under nitrogen conditions, 8 mmol BADPS, 12 mmol NaOt-Bu, 0.04 mmol Pd2(dba)3, 0.12 mmol BINAP and 20 mL N,N-dimethylformamide were added to a 50 mL three-necked flask in sequence, mixed, and then heated to 125°C for continuous reaction for 11 hours. After the reaction, the obtained polymer solution was poured into ice water and stirred to precipitate a brown solid. The filter cake was filtered and washed with water to obtain a filter cake, which was dried in a vacuum drying oven. The dried filter cake was extracted with methanol as an extractant using a Soxhlet extraction apparatus for 12 hours to remove unreacted small molecules and impurities. After vacuum drying, polyiminosulfone (PIS) was obtained.

[0071] Example 3

[0072] A dual-mode stimulus-responsive polymer, the preparation method of which comprises the following steps:

[0073] (1) 3 g (13.5 mmol) of p-nitrobenzenesulfonyl chloride, 1.67 g (12.5 mmol) of aluminum chloride and 8 mL of bromobenzene were added to a 50 mL two-necked flask, stirred at room temperature for 2 h, and then slowly heated to 65° C. for reaction for 5 h. After the reaction was completed, the reaction solution was poured into ice water and stirred for 30 minutes. After the precipitated solid (light yellow) no longer increased, it was filtered and vacuum dried (60° C., 10 h) to obtain crude 4-bromo-4'-nitrodiphenyl sulfone (BNDPS), which was purified by recrystallization from ethanol to obtain 4-bromo-4'-nitrodiphenyl sulfone (BNDPS), i.e., intermediate 1;

[0074] (2) 3.23 g (13.45 mmol) of Na2S·9H2O, 0.52 g (16.25 mmol) of sulfur powder and 25 mL of deionized water were added to a 50 mL double-necked flask containing 0.5 mol / L sodium polysulfate (Na2S2) solution, and then heated to 90°C to completely dissolve the sublimated sulfur powder to prepare a sulfur-containing solution;

[0075] 2.24 g of BNDPS was added to a 100 mL double-necked flask, and then the sulfur-containing solution was slowly added and heated to 94 ° C for 2 h. After the reaction was completed, the excess Na2S2 was removed by water washing and vacuum drying (60 ° C, 10 hours), and 4-bromo-4'-aminodiphenyl sulfone (BADPS) was obtained by recrystallization and purification by ethanol, i.e., intermediate 2;

[0076] (3) Under nitrogen conditions, 8 mmol BADPS, 12 mmol NaOt-Bu, 0.04 mmol Pd2(dba)3, 0.12 mmol BINAP and 20 mL N,N-dimethylformamide were added to a 50 mL three-necked flask in sequence, mixed, and then heated to 135°C for continuous reaction for 11 hours. After the reaction, the obtained polymer solution was poured into ice water and stirred to precipitate a brown solid. The filter cake was filtered and washed with water to obtain a filter cake, which was dried in a vacuum drying oven. The dried filter cake was extracted with methanol as an extractant using a Soxhlet extraction apparatus for 12 hours to remove unreacted small molecules and impurities. After vacuum drying, polyiminosulfone (PIS) was obtained.

[0077] Example 4

[0078] A dual-mode stimulus-responsive anti-counterfeiting film, the preparation method of which comprises the following steps:

[0079] Weigh polyetheramine D400 (2.00 g, 5 mmol) and bisphenol A diglycidyl ether E51 (1.96 g, 10 mmol) and add them into 20 mL DMF, and subject the solution to ultrasonic treatment for uniform dispersion to obtain a matrix material solution (EPD); prepare a 30 mg / ml solution of PIS powder, and then take 132 μL and drop it into the matrix material solution, homogenize to obtain an EPD-1% solution; pour the EPD-1% solution onto a clean glass slide, and dry it at 80°C to obtain a dual-mode stimuli-responsive anti-counterfeiting film.

[0080] Test example

[0081] 1. PIS's color change reaction

[0082] The color change mechanism of PIS was studied using the model compound phenyl (4-(phenylamino)phenyl) methyl sulfone. The color change mechanism of PIS under acid-base stimulation was verified. The optimized energy of the nitrogen anion (transition state) and quinone structure of the PIS model compound as well as the changes in HOMO and LUMO energy levels were calculated using Gaussian software (see Figure 4 );

[0083] The results show that after protonation and further formation of the quinone structure, the energy of the model compound is significantly reduced compared to the first two structures, indicating that the structure is more stable, that is, the quinone structure has the lowest energy and is the most stable. The transition from PIS to the quinone structure involves a change in the molecular structure that extends the conjugated system, increases the delocalization of electrons, and enhances the intramolecular charge transfer (ICT) effect. This leads to a decrease in the energy gap between HOMO and LUMO, indicating that the formation of the quinone structure enhances the conjugation effect, increases the intramolecular charge transfer effect, and leads to a decrease in absorption and emission energy, resulting in a decrease in energy absorption and emission photons and a significant red shift in the spectrum. This finding provides strong evidence for the stimulus-induced color change mechanism of PIS.

[0084] Taking PIS in Example 1 as an example, UV-visible absorption spectroscopy was used to analyze the color change of PIS when it was exposed to alkaline stimulation. PIS was dissolved in DMF, and then different amounts of NaOt-Bu (NaOt-Bu:PIS=1:10, 1:20 and 1:30) were added (see Figure 5 ), the results show that initially, the maximum absorption peak of the solution (λ 最大限度 Located at 363nm, with the increase of NaOt-Bu content, the peak at 363nm decreases, and a new absorption peak appears at a longer wavelength. When NaOt-Bu:PIS=1:20, λ 最大限度 When NaOt-Bu:PIS=1:30, it shifted to 484nm and stabilized there. To verify the reversibility of this color change, NaOt-Bu and CF3COOH were added to the PIS solution for multiple cycles and UV spectra were recorded. Each cycle showed that the λ 最大限度 From 363nm to 484nm (see Figure 6 ), the solution quickly changed from colorless to bright yellow (see Figure 7 ). Adding CF3COOH can reverse this situation and make λ 最大限度 Return to 363nm and quickly restore the color. This process can be repeated for at least 10 cycles (see Figure 8 ).

[0085] Due to the presence of donor-π-acceptor (D-π-A) structure in PIS, PIS also exhibits significant photoluminescence in DMF. Before adding NaOt-Bu, the PIS solution has a maximum emission peak at 380 nm (see Fig. 9 ), showing purple fluorescence; adding NaOt-Bu shifted the peak to 508 nm, indicating a red shift and changing the fluorescence from purple to green; Fig. 9 The chromaticity (CIE) diagram inserted in the figure clearly demonstrates the high-contrast fluorescence change of PIS under alkaline stimulation, which provides a significant advantage for anti-counterfeiting applications.

[0086] To evaluate PIS as a dual-mode stimuli-responsive material, fluorescence spectroscopy was performed using multiple cycles of NaOt-Bu and CF3COOH. The addition of NaOt-Bu reduced the fluorescence emission at 380 nm and introduced a new peak at 508 nm, changing the color from purple to green. This was reversed by the addition of CF3COOH (see Fig.10 ), restoring fluorescence emission and color. This process can be repeated for at least 10 cycles, demonstrating the reproducibility of PIS (see Fig.11 ). Overall, the spectroscopic results confirm the potential of PIS as a dual-mode stimuli-responsive material with excellent reversibility, repeatability, and high contrast.

[0087] Taking the PIS prepared in Example 1 as an example, it was diluted to prepare solutions of different concentrations, and then fluorescence tests were performed. The specific results are shown in Fig.12 ;

[0088] It can be seen that PIS exhibits strong fluorescence in dilute solutions, with the maximum intensity observed at a concentration of 0.005 mg / mL. When the concentration exceeds 0.1 mg / mL and in solutions with higher concentrations, the luminescence of PIS is significantly weakened or almost disappears. Therefore, PIS can be used as a trace stimuli-responsive polymer.

[0089] 2. Thermal stability of PIS

[0090] Taking the PIS prepared in Example 1 and the existing stimuli-responsive color-changing materials as examples, TGA and DSC analysis were used to evaluate the thermal stability of PIS; the TGA curve (see Fig.13 a) shows that PIS exhibits a 5% weight loss temperature (T5%) at 463°C and a 50% weight loss at 800°C under nitrogen conditions. Fig.13 c) shows a clear endothermic step, indicating that the glass transition temperature (Tg) of PIS is 245 °C. It is worth noting that Fig.13 As shown in Figures 1b and 13d, PIS exhibits excellent thermal stability compared to other polymers with stimuli-responsive color-changing capabilities. This exceptional Tg may be attributed to the strong hydrogen bonding within the polymer chain. In conclusion, PIS was confirmed to be a thermally stable material, highlighting its potential for advanced applications.

[0091] 3. PIS can be used as a multifunctional stimuli-responsive material with repeatability. This unique property helps to implement a complex double encryption system to ensure high confidentiality and security of information (see Fig.14 ). In an encrypted state, information remains hidden ( Fig.14 a), can be accessed using three different methods: 1. ethanol (EtOH), 2. PIS+H +and 3.PIS solution. Moreover, under UV light, the information can be reversibly switched between "false information" and "true information". When the initial encrypted message is exposed to UV light, an error message "88" ( Fig.14 b). By adding equal amounts of alkaline (NaOt-Bu / NaOH) substances to the three solutions simultaneously, the hidden phenomenon will be revealed. Under visible and UV light, messages 2.1 "11" and 2.2 "EE" will appear. This is due to the obvious color gradation and fluorescence changes of the PIS solution in an alkaline environment ( Fig.14 c and 14d). Furthermore, by neutralizing the alkaline material with an acid (e.g., CF3COOH), the system is restored to its original state. This double encryption confidentiality system is completely recyclable, providing a powerful and reusable method for information security.

[0092] 4. Taking the method for preparing the anti-counterfeiting film in Example 4 as an example, different proportions of PIS were added to produce a series of PIS-doped epoxy resin films (EPD-x%), and the performance of the prepared resin films was verified; wherein, the process diagram of preparing epoxy resin film (EPD) from polyetheramine D400 and bisphenol A diglycidyl ether E51 (see Fig.15 );

[0093] The color change of the anti-counterfeiting film under different PIS doping ratios (see Fig.16 ) The results showed that both the pure EPD film and the PIS-doped EPD film were colorless and transparent under visible light. However, under 365nm UV light, the EPD-x% film exhibited strong purple fluorescence, consistent with the fluorescence observed in the PIS solution; after immersion in an alkaline solution, the pure EPD film remained unchanged, while the EPD-x% film clearly changed from colorless to yellow. In addition, under UV irradiation, the fluorescence of the EPD-x% film changed dramatically from purple to green, while the pure EPD film had no fluorescence. It is worth noting that even with only 0.1% PIS, the EPD-x% film exhibited obvious fluorescence and color transition, indicating that even the smallest amount of PIS can effectively impart color-changing behavior to the epoxy resin.

[0094] The EPD-0.3% film undergoes fluorescence color changes in response to alkaline and acidic conditions (see Fig.17 ) The results showed that as the film thickness decreased, the reaction could be faster, highlighting its fast response capability.

[0095] PIS was introduced into the anti-counterfeiting film in the form of a pattern, and a color development experiment was conducted on the anti-counterfeiting film (see Fig.18), the results showed that under visible light, the film appeared uniformly transparent, but ultraviolet irradiation showed a clear pattern in the doped area. After exposure to an alkaline solution, a yellow pattern appeared under visible light, while a green pattern appeared under ultraviolet light. Subsequent treatment with an acidic solution restored the film to its original state, achieving an effective dual anti-counterfeiting function.

[0096] Stress-strain curves of EPD-x% films (see Fig.19 ) The results showed that increasing the PIS content from 0.1% to 1% slightly enhanced the film strength while causing a slight decrease in the elongation at break. This improvement was attributed to the formation of hydrogen bonds between the -NH and -SO2- groups of PIS and the -O- and -OH groups of EPD, providing micro-crosslinks within the matrix.

[0097] DSC curve of EPD-x% film (see Fig. 20 ); TGA curve of EPD-x% film (see Fig.21 ); The results show that the glass transition temperature (Tg) and 5% decomposition temperature (T5%) increase with the increase of PIS content compared with pure EPD film. The enhancement of thermal properties is due to the hydrogen bonding cross-linking between PIS and EPD, which restricts the mobility of molecular chains.

Claims

1. A dual-mode stimulus-responsive polymer, characterized in that: The structural formula of the polymer is: Among them, n is 30.

2. The method for preparing a dual-mode stimulus-responsive polymer according to claim 1, wherein: The following steps are involved: (1) p-nitrobenzenesulfonyl chloride, aluminum chloride and bromobenzene are stirred and mixed, and the mixture is heated to react. After the reaction is completed, the reaction solution is placed in ice water to precipitate, and the precipitate is dried and purified to obtain intermediate 1; (2) adding Na2S·9H2O, sulfur powder and deionized water to a sodium polysulfate solution and heating until dissolved to prepare a sulfur-containing solution; (3) adding the intermediate of step (1) to the sulfur-containing solution of step (2), heating for reaction, collecting the precipitate after the reaction, removing the excess sodium polysulfate, and purifying to obtain intermediate 2; (4) Under nitrogen conditions, the intermediate 2, NaOt-Bu, Pd2(dba)3, BINAP and N,N-dimethylformamide were mixed and heated to react. After the reaction was completed, the mixture was placed in ice water to precipitate, and purified to obtain the product.

3. The method for preparing a dual-mode stimulus-responsive polymer according to claim 1, wherein: In step (1), the heating reaction temperature is 55-65° C. and the reaction time is 5-7 h.

4. The method for preparing a dual-mode stimulus-responsive polymer according to claim 1, wherein: In step (3), the heating reaction temperature is 90-94° C. and the reaction time is 2-3 h.

5. The method for preparing a dual-mode stimulus-responsive polymer according to claim 1, wherein: In step (1) and step (3), ethanol is used for recrystallization purification.

6. The method for preparing a dual-mode stimulus-responsive polymer according to claim 1, wherein: In step (4), the heating reaction temperature is 125-135° C. and the reaction time is 11-13 h.

7. The method for preparing a dual-mode stimulus-responsive polymer according to claim 1, wherein: In step (4), methanol is used for recrystallization purification.

8. Use of the dual-mode responsive polymer described in claim 1 in the preparation of anti-counterfeiting materials.

9. A dual-mode responsive anti-counterfeiting film comprising the dual-mode stimulus responsive polymer described in claim 1.

10. The method for preparing the dual-mode stimulus-responsive anti-counterfeiting film according to claim 9, characterized in that: The following steps are involved: The PIS is added into the polymer matrix solution, stirred and mixed to obtain a mixture solution, and the mixture solution is coated on a substrate and dried to obtain the product.